ПРОЦЕСУАЛЬНЬІЙ ПІДХІД В ОРГАНІЗАЦІЇ НАВЧАННЯ НА УРОКАХ ГЕОГРАФІЇ (Педагогіка вищої та середньої школи, 2009)
The theoretical analysis of the processual approach problem in the organizing of the learning process at the geography lessons has been given in the article; the different forms and methods of the organizing of the learning process at the geography lessons have been shown.